2023
DOI: 10.3390/biomedicines11102749
|View full text |Cite
|
Sign up to set email alerts
|

The Complicated Relationship of Short-Chain Fatty Acids and Oral Microbiome: A Narrative Review

Georgy E. Leonov,
Yurgita R. Varaeva,
Elena N. Livantsova
et al.

Abstract: The human oral microbiome has emerged as a focal point of research due to its profound implications for human health. The involvement of short-chain fatty acids in oral microbiome composition, oral health, and chronic inflammation is gaining increasing attention. In this narrative review, the results of early in vitro, in vivo, and pilot clinical studies and research projects are presented in order to define the boundaries of this new complicated issue. According to the results, the current research data are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 148 publications
0
6
0
Order By: Relevance
“…Despite numerous studies devoted to AD, a precise mechanism for the disease development still needs to be discovered. The scientific community currently targets the microbiome as a critical point in various diseases [ 34 ], including AD pathogenesis. This performed study provides the oral microbiome compartment peculiarities in Kazakhstanis in the interactions with clinical, demographic, and anamnestic data and laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous studies devoted to AD, a precise mechanism for the disease development still needs to be discovered. The scientific community currently targets the microbiome as a critical point in various diseases [ 34 ], including AD pathogenesis. This performed study provides the oral microbiome compartment peculiarities in Kazakhstanis in the interactions with clinical, demographic, and anamnestic data and laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…46 Most are oral facultative anaerobic organisms which are capable of producing SCFAs though oral concentrations are much less than colonic. 42,47 Several studies have indicated that SCFAs stimulate propulsive motility in the terminal ileum 36 while in the colon they may both inhibit and stimulate propulsive motility depending on the type and concentration. 48 SCFAs act by activating the G protein coupled receptors (GPRs), GPR41 and GPR43 which are expressed on Peptide YY containing enteroendocrine cells in rats 49 and humans.…”
Section: Ta B L Ementioning
confidence: 99%
“…Streptococcus, a heterogeneous group, is the most common genera found in oral cavity, which can colonize on hard tissue, soft tissue, and is present in saliva [18]. HOMD lists firmicutes (genera streptococcus and granulicatella), Actinobacteria (genera corynebacterium, Rothia, Actinomyces), Fusobacteria (genera fusobacterium), Bacteroidetes (genera Prevotella, Capnocytophaga, Porphyromonas) and Proteobacteria (genera Neisseria, Haemophilus) as most prevalent phyla of adult human oral cavity [19]. A reliable relationship was established between oral microbiome and systemic diseases, including cardiovascular diseases [20], neurodegenerative diseases [21], rheumatoid arthritis [22], preterm birth [23], cancers [7] and inflammatory bowel disease [24].…”
Section: Healthy Commensal Oral Microbiomementioning
confidence: 99%